The bloodsucking biting midges of Argentina (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2005)
A key is presented for the identification of the adults of 54 species of bloodsucking ceratopogonids, 51 of which are known inhabitants of Argentina, and Culicoides uruguayensis Ronderos, C. pifanoi Ortiz, and C. trilineatus Fox, which are known to occur in bordering Uruguay and Paraguay. Wing photographs are provided of females of the 45 species of Culicoides. Three new species of Culicoides Latreille from Northeastern Argentina are described and illustrated: C. austroparaensis Spinelli, C. bachmanni Spinelli, and C. williamsi Spinelli. The following six species are recorded for the first time from Argentina and/or bordering localities in Paraguay: Leptoconops brasiliensis (Lutz), C. gabaldoni Ortiz, C. ginesi Ortiz, C. pifanoi Ortiz, C. pseudocrescentis Tavares and Luna Dias, and C. trilineatus; and C. estevezae Ronderos and Spinelli is newly recorded from Misiones province of Argentina. C. lopesi Barretto is excluded from the Argentinean ceratopogonid fauna.